Creation of a comfortable psychological climate in university teaching staff - Anatoliyevna Repkina, Yulia (2021)
The article is devoted to improving the psychological climate in university teaching staff. The article provides a theoretical analysis of the considered phenomenon, its connection with the phenomenon of communications, and its elaboration in the pedagogical and psychological research. The study highlights the importance of socio-psychological climate in the context of the effectiveness of the activities of teachers and teaching staff in general. The study is aimed at examination of the problem of improvement of psychological climate in university teaching staff. To achieve the goal of the research, the authors developed and carried out an experiment aimed at examination of the ways to improve the psychological climate in university teaching staff with the help of training activity. The authors selected the research methodology and its algorithm, including a complex psychological and pedagogical experiment and tracking the state and dynamics of socio-psychological climate in university teaching staff before and after the formative influence. The research was carried out during one semester at the Institute of Foreign Languages of the Peoples’ Friendship University of Russia. The study involved 40 teachers; the sample was representative in terms of gender and other characteristics. The results of the study allow concluding that training is an effective method of improving the socio-psychological climate in university teaching staff under several significant conditions.